RELATIONSHIP ALGEBRAIC EQUATIONS WITH (N,M)-FORMS, THEIR DEGREES AND RECURRENCE FRACTIONS - Заторський, Роман Андрійович; Ліщинський, Іван Іванович; Семенчук, Андрій Васильович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
It analyzes the relationships (n,m)-forms type $s_0 + s_1 \sqrt[n]{m} +… + s_{n − 1} \sqrt[n]{m^{n−1},$ $s_i , m\in Q$ with the generalized Diophantine equations Pell, algebraic equations n-th degree and recurrence fractions.